PEMBERDAYAAN DANA DESA TERHADAP KESEJAHTERAAN MASYARAKAT DI DESA PANCIRO KECAMATAN BAJENG KABUPATEN GOWA (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2022)
This study describes the main problem "How is Village Fund Empowerment on Community Welfare in Panciro Village, Bajeng District, Gowa Regency?" With sub-problems, namely: How is Village Fund Empowerment on Community Welfare in Panciro Village, Bajeng District, Gowa Regency? and What are the obstacles faced in Empowering Village Funds on Community Welfare in Panciro Village, Bajeng District, Gowa Regency? The results of this study indicate that the implementation of the village fund empowerment program in Panciro Village which is run by the Panciro village apparatus is in accordance with government regulations and there have been several successful programs run. The obstacles that often arise are due to the lack of synchronic coordination between the government and regional confusion, the distribution of village funds is hampered and the impact is that the wheels of the village economy are hampered. Keywords: Village Fund, Community Welfare, Panciro Village